Branched ultra-fine nickel oxide/manganese dioxide core–shell nanosheet arrays for electrochemical capacitors. Issue 94 (14th October 2015) - Li, Yanhong; Peng, Huarong; Zhang, Chao; Chu, Mengsha; Xiao, Peng; Zhang, Yunhuai
<x xml:space="preserve">Abstract</x> Hierarchically core–shell structure composed of two dimensional NiO and MnO2 nanosheets demonstrate good electrochemical performance in supercapacitor.